Increased Arterial Stiffness is Associated with Poor Collaterals in Acute Ischemic Stroke from Large Vessel Occlusion - Acampa, Maurizio; Romano, Daniele G.; Lazzerini, Pietro Enea; Leonini, Sara; Guideri, Francesca; Tassi, Rossana; Casseri, Tommaso; Bracco, Sandra; Martini, Giuseppe (Current Neurovascular Research, 2018)
Background: Cerebral collateral circulation is a network of arterial anastomotic channels capable of providing supplementary perfusion to brain regions in response to ischemic insults. Arterial stiffness could negatively affect collateral circulation development, by means of its effects on the structural intracerebral vasculature. Objective: The aim of our study is to investigate a possible link between arterial stiffness and presence of collateral circulation in patients with acute ischemic stroke. Methods: 113 patients (age: 74±12 years) with acute anterior ischemic stroke underwent neuroimaging examination and 24-hour blood pressure monitoring. Arterial Stiffness Index (ASI) and Pulse Pressure (PP) were assumed as surrogate measures of arterial stiffness. Collateral circulation was evaluated by means of the collateral grading system that was scored on a scale of 0–3. Results: According to TOAST classification, etiology of ischemic stroke was the following: Large-Artery Atherosclerosis (LAA)(n:41), Cardioembolism (CE)(n:60), Undetermined Etiology (UE)(n:12). Logistic regression analysis showed that good predictors of poor collaterals were ASI (OR 2.78 for 0.1, 95% CI:1.19–6.50, p=0.01) and PP (OR 1.81 for 10 mmHg, 95% CI:1.01–3.22, p=0.04) in stroke from LAA. Conclusion: Our results suggest that, in patients with ischemic stroke from LAA, arterial stiffness may contribute to the impairment of collateral circulation and, therefore, it could reduce the beneficial effects of acute treatments.
Keywords: CT-angiography